The F11 receptor (F11R/JAM-A) in atherothrombosis: Overexpression of F11R in atherosclerotic plaques - Babinska, Anna; Azari, Bani M.; Salifu, Moro O.; Liu, Ruijie; Jiang, Xian-Cheng; Sobocka, Malgorzata B.; Boo, Dorothy; Khoury, George AI; Deitch, Jonathan S.; Marmur, Jonathan D.; Ehrlich, Yigal H.; Kornecki, Elizabeth (Thrombosis and Haemostasis, 2007)
F11R is the gene name for an adhesion protein, called the F11-receptor, aka JAM-A, which under normal physiological conditions is expressed constitutively on the surface of platelets and localized within tight junctions of endothelial cells (EC). Previous studies of the interactions between human platelets and EC suggested that F11R/JAM-A plays a crucial role in inflammatory thrombosis and atherosclerosis. The study reported here obtained in-vivo confirmation of this conclusion by investigating F11R/JAM-A protein and mRNA in patients with aortic and peripheral vascular disease and in an animal model of atherosclerosis. Molecular and immunofluorescence determinations revealed very high levels of F11R/JAM-A mRNA and F11R/JAM-A protein in atherosclerotic plaques of cardiovascular patients. Similar results were obtained with 12-week-old atherosclerosis-prone apoE-/- mice, an age in which atherosclerotic plaques are well established. Enhanced expression of the F11R/JAM-A message in cultured EC from human aortic and venous vessels was observed following exposure of the cells to cytokines. Determinations of platelet adhesion to cultured EC inflamed by combined cytokine treatment in the presence of F11R/JAM-A – antagonists provided data indicating that de novo expression of F11R/JAM-A on the luminal surface of inflamed EC has an important role in the conversion of EC to a thrombogenic surface. Further studies of these interactions under flow conditions and under in-vivo settings could provide a final proof of a causal role for F11R/JAM-A in the initiation of thrombosis. Based on our invitro and in-vivo studies to date, we propose that therapeutic drugs which antagonize the function of F11R/JAM-A should be tested as novel means for the prevention and treatment of atherosclerosis, heart attacks and stroke.
Keywords: F11R; F11 receptor; F11R/JAM-A; inflammatory thrombosis; atherosclerosis; atherothrombosis